Tahun Politik, Komunikasi Konfrontatif - Pareno, Sam Abede (representamen, 2018)
Term â€œConfrontative Communicationâ€ popular in Indonesia when the election of Governor ofJakarta at 2012. In that year, one candidate often talk intimidation people and his competitor withusing sarcastic sentence, for example â€œIf you will not choose Betawi man, please out from Jakarta orI will disarm your facilities included your KTP (kartu tanda penduduk, identification card)â€.Confrontative Communication different with Confrontation Communication in medical work which isdone by doctor or nurse. Confrontative Communication is a part of coersive communication which isused in political communication. Every candidate use confrontative communication to defeatcompetitor; among them use it each other.Now, in the politics year for winning the election especially president election, confrontativecommunication without controlled by politics ethics tends to be used in political communication. Thisarticle want to clarify that phenomena.Key words: political communication, coersive communication, confrontative communication.